Longitudinal Associations of Social Anxiety Trajectories with Internet-Related Addictive Behaviors Among College Students: A Five-Wave Survey Study. - Li, Xiaomeng; Chen, Xiaoyan; Zhu, Ya; Shi, Xuliang (International Journal of Mental Health & Addiction, 2025)
The college stage is characterized by increased interpersonal interaction and intense social anxiety. Although the associations between social anxiety and internet-related addictive behaviors have been established, the question of whether the developmental trajectory of social anxiety is linked to subsequent internet-related addictive behaviors remains unexplored. Utilizing a longitudinal design combined with a person-centered approach, the current study examined the developmental trajectory of social anxiety among 3,861 students throughout their university years. Additionally, we explored the impacts of specific change patterns of social anxiety on subsequent internet-related addictive behaviors. The growth mixture modeling identified three distinct profiles of social anxiety: high-stable group (n=515, 13.33%), high-decreasing group (n=243, 6.30%), and low-decreasing group (n=3103, 80.37%). Furthermore, the results of binary logistic regression analysis revealed that students in the high-decreasing and low-decreasing groups were less likely to experience smartphone addiction and Internet game addiction compared to those in the high-stable group. These findings underscore the importance of identifying individuals with a high risk for social anxiety and providing them with personalized and effective mental health services to mitigate their susceptibility of developing internet-related addictive behaviors.